2019
DOI: 10.1093/tbm/ibz012
|View full text |Cite
|
Sign up to set email alerts
|

Cancer genetic health communication in families tested for hereditary breast/ovarian cancer risk: a qualitative investigation of impact on children’s genetic health literacy and psychosocial adjustment

Abstract: Parents and providers can support children's genetic health literacy and psychosocial adjustment to hereditary breast/ovarian cancer (HBOC) risk information through open family communication.Policy: Public health benefits from genetic testing for HBOC mutations may only be realized when all high-risk relatives of individual mutation carriers are informed of their family's status, including children, so that appropriate risk-reducing steps can be considered at different life stages.Research: Future research is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 43 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, our study cohort was likely to inherit a selection bias toward participants prone to above-average health habits, as it has been shown that a prior cancer disease is likely to have confounding effects on subsequent health behavior [ 70 ]. Especially the fact that a g BRCA1/2 mutation or cancer diagnosis often occurs within the familial surrounding, participants—whether themselves diseased or not—are likely to be sensitized for a more proactive engagement toward lifestyle changes [ 71 ]. We also did not control for special dietary habits or sport programs of the participants prior to SE, hence we could not account for potentially confounding and/or prolonging effects of individual health behavior on the biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study cohort was likely to inherit a selection bias toward participants prone to above-average health habits, as it has been shown that a prior cancer disease is likely to have confounding effects on subsequent health behavior [ 70 ]. Especially the fact that a g BRCA1/2 mutation or cancer diagnosis often occurs within the familial surrounding, participants—whether themselves diseased or not—are likely to be sensitized for a more proactive engagement toward lifestyle changes [ 71 ]. We also did not control for special dietary habits or sport programs of the participants prior to SE, hence we could not account for potentially confounding and/or prolonging effects of individual health behavior on the biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as information needs may be related to counselees’ characteristics such as their age [ 17 ], level of education [ [33] , [34] , [35] ], parental status [ 17 ], exposure to familial experience with BC [ 28 ], cancer risk perceptions [ 36 ], distress [ 19 ] and coping modalities [ 37 , 38 ], these aspects were further explored to identify subgroups of counselees particularly in need for enhanced communication and additional information on BC GRF and NGRF.…”
Section: Introductionmentioning
confidence: 99%
“…The next article by Tercyak et al [17] examines qualitative responses from adolescents and young adults with a parent that received genetic testing for hereditary breast and ovarian cancer risk. There are currently no guidelines for when and how minor children should be informed about hereditary breast and ovarian cancer risk, particularly when genetic testing for this risk is typically only offered to adults.…”
mentioning
confidence: 99%
“…There are currently no guidelines for when and how minor children should be informed about hereditary breast and ovarian cancer risk, particularly when genetic testing for this risk is typically only offered to adults. Tercyak et al [17] found that children responded to receiving information about their parent's hereditary breast and ovarian cancer risk in diverse ways, including demonstrating resilience in coping with the information. The findings also indicated that some children had misconceptions or inaccurate conclusions about the increased cancer risk [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation